Poverty Alleviation and Equity Promotion - Edwin del Valle; Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 1998)
Recent Philippine data indicate that the needs of the poor, which are met unsatisfactorily, include productive employment, access to quality education, access to basic health services, potable water, sanitation facilities and electricity. This paper emphasizes that eradicating poverty entails effective poverty alleviation strategy as an integral part of the government programs. Strategies should be focused on broad-based economic growth for employment generation and livelihood opportunities. It also offers measures to aid poor people during the transition period.
Keywords: 330; poverty alleviation; poverty gap